Actein Inhibits the Proliferation and Adhesion of Human Breast Cancer Cells and Suppresses Migration in vivo - Wu, Xiao-Xiao; Yue, Grace Gar-Lee; Dong, Jin-Run; Lam, Christopher Wai-Kei; Wong, Chun-Kwok; Qiu, Ming-Hua; Lau, Clara Bik-San (Frontiers in Pharmacology, 2018)
Background and purpose: Metastasis is an important cause of death in breast cancer patients. Anti-metastatic agents are urgently needed since standard chemotherapeutics cannot diminish the metastatic rate. Actein, a cycloartane triterpenoid, has been demonstrated to be anti-angiogenic and anti-tumor. Its anti-metastatic activity and underlying mechanisms were evaluated in the present study. Methods: A human metastatic breast cancer cell xenograft model was established in transparent zebrafish embryos to examine the anti-metastatic effect of actein in vivo. Its in vitro effects on the proliferation, cell cycle phase distribution, migration, motility and adhesion were evaluated using two human breast cancer cell lines, MDA-MB-231 (estrogen receptor-negative) and MCF-7 cells (estrogen receptor-positive). Western blots and real-time PCR were employed to examine the protein and mRNA expression of relevant molecules. Results: Actein (60 µM) significantly decreased the number of zebrafish embryos with migrated cells by 74% and reduced the number of metastatic cells in embryos. In vitro experiments showed actein treatment significantly decreased cell proliferation, migration and motility. Furthermore, actein significantly caused G1 phase cell cycle arrest and suppressed the protein expression of matrix metalloproteinases of MDA-MB-231 cells. Actein treatment down-regulated the protein expression of epidermal growth factor receptor (EGFR) and cofilin together with the up-regulation of related proteins and kinases in cofilin pathway. Conclusion: Actein exhibited both in vivo and in vitro anti-metastatic activities, with the underlying mechanisms involved the cofilin signalling pathway. These findings shed light for the development of actein as novel anti-metastatic natural compound for advanced breast cancer.